صور التواصل بين الغرب الإسلامي والمشرق على ضوء رحلة ابن جبير الأندلسي(540هـ -1145م/614هـ -1217م) - نجوى سايح; يسرى مصباحي (جامعة الوادي - University of Eloued, 2025)
تناولنا في هذا البحث صور التواصل بين الغرب الاسلامي والمشرق من خلال رحلة ابن جبير ، ولقد حاولنا تسليط الضوء على أهم جوانب هذا التواصل، فاعتمدنا استقراء رحلة ابن جبير واستخراج المادة العلمية منها المتعلقة بالعلاقات بين المنطقتين، فعرضنا علاقات السياسية للموحدين بالأيوبيين ،بالإضافة إلى تفاعل المغاربة العسكري مع الحروب الصليبية. كما تتبع البحث الروابط الاقتصادية من خلال النشاط الزراعي والصناعي والتجاري. وسعى إلى إبراز مظاهر التفاعل الاجتماعي والحضاري من خلال كرم الضيافة، دور المرافق، وأهمية الرحلة الحجازية وحضور المذهب المالكي والمشاهد المقدسة والمراكز العلمية. قدم البحث إلى رؤية شاملة لتفاعلات بين بلدان الغرب الاسلامي والمشرق في تلك الفترة التاريخية، بالإضافة إلى ذلك، عرفنا بجهود المغاربة والمشارقة في التفاعل والتأثير المتبادل في مختلف المجالات. This research explores the facets of communication between Islamic West and the Mashriq through the journey of Ibn Jubayr. We have endeavored to shed light on the most significant aspects of this interaction, relying on the extrapolation of Ibn Jubayr's travels and the extraction of scholarly material pertaining to the relations between the two regions. Consequently, we presented the political relations of the Almohads with the Ayyubids, in addition to the Maghrebi military involvement in the Crusades. The research also traced the economic links through agricultural, industrial, and commercial activities. Furthermore, it sought to highlight the manifestations of social and cultural interaction through hospitality, the role of social facilities, the importance of the Hajj pilgrimage, the presence of the Maliki school of thought, holy sites, and intellectual centers. This study provides a comprehensive vision of the interactions between the Islamic West and the Mashriq during that historical period. Moreover, we identified the efforts of the Maghrebis and Mashriqis in mutual interaction and influence across various fields.
مذكرة ماستر قسم علوم انسانية تخصص تاريخ الغرب الإسلامي في العصر الوسيط
Keywords: ابن جبير; الغرب الاسلامي; المشرق الاسلامي; تفاعل; تواصل; Communication; Interaction; Islamic Mashriq; the Islamic West; Ibn Jubayr.